A case report of left ventricular lead implantation via total three-dimensional transseptal puncture after tricuspid valve replacement - Gao, Jia; Zhang, Nan; Zhang, Binghang; Sun, Meng; Meng, Zhijun; Guo, Min; Wang, Rui (Frontiers in Cardiovascular Medicine, 2023)
Background: Ventricular lead implantation is relatively difficult for patients with bradyarrhythmia after tricuspid valve replacement. Right atrial (RA) abnormalities often occurred in patients with tricuspid valve disease; conventional coronary sinus (CS) lead implantation is not easy to operate. Therefore, it is necessary to develop a safe method for implanting LV endocardial leads in patients after tricuspid valve replacement. Case presentation: A 76-year-old Asian woman who had been implanted with a metal tricuspid valve replacement 4 years ago was admitted to the Department of Cardiology for pacemaker implantation due to transient blackout related to persistent atrial fibrillation with long pauses. The patient's family rejected the surgical placement of an epicardial LV lead. Therefore, we first intended to operate LV lead implantation through the CS; however, the orifice of the CS was virtually difficult to seek. Ultimately, we utilized total 3-dimensional (T3D) transseptal puncture (TSP) under the guidance of the CARTO 3 system; thus, we implanted the LV endocardial lead, which contributed to the accurate puncture of the central fossa ovalis and ensured the safety of TSP in the case of RA enlargement. Meanwhile, the CARTO 3 system contributed to the localization of the LV lead to the LV free wall during implantation. All the intraoperative and postoperative pacemaker parameters were favorable; no intraoperative or postoperative complications occurred. Conclusions: This case report may provide a novel surgical approach for LV lead implantation in patients who underwent tricuspid valve replacement or patients who may benefit from cardiac resynchronization therapy but failed to implant CS lead.